Hot corrosion behaviors of as-sprayed and laser-remelted YSZ thermal barrier coatings at 950 °C - Yang,Z.G. (2022)
ABSTRACT In the current study, the influences of laser remelting treatment on NiCoCrAlY/ZrO2-7 wt.% Y2O3 thermal barrier coatings fabricated via plasma spraying on GH4169 alloy were examined. The microstructure, microhardness, hot corrosion resistance at 950 ℃ of the two types of TBCs were investigated comparatively. The results indicated that the as-sprayed TBCs had a lamellar structure with high cracks and porosity. After laser remelting treatment, a laser remelted layer with a compact sub-micro sized grains arranged in a stacked structure was formed which was denser than that of the as-sprayed TBCs. The surface microhardness of the as-sprayed TBC was only 977 HV0.3, which exhibited a significant increase (over 1500 HV0.3) after laser remelting due to the fine grains of the remelted region with lower porosity. The hot corrosion resistance of the laser remelted TBCs were considerably better than the as-sprayed one. The as-sprayed TBC with a lot of defects, the molten salts could easy penetrate the coating and react with Y2O3. The consumption of Y element promoted the phase transition of t'-ZrO2 to m-ZrO2, which harmed the protective coating because of the volume expansion of the phase transition. The laser remelted TBCs was dense, which could significantly reduce the penetrate of molten salts due to the fewer cracks and holes compared to the as-sprayed TBCs. The laser remelted TBCs exhibited superior hot corrosion performance as compared to the as-sprayed TBCs.